Essay/Review: Vita Mathematica - Radford, Luis (Revista Brasileira de História da Matemática, 2020)
Historical Research and Integration with Teaching. Ronald Calinger, Editor. Washington DC: The Mathematical Association of America. xii + 359 pp. ISBN 0-88385-097-4